Peran Qanun dan Reusam terhadap Penanganan Anak yang Berhadapan dengan Hukum di Aceh - Rini Anggreini; Devi Yulida (Fakultas Hukum, Universitas Warmadewa, 2025)
Indonesia, as a unitary state, recognizes the importance of regional diversity within its governance system, exemplified by the implementation of regional autonomy. This policy grants local governments the authority to manage certain affairs in accordance with the needs of local communities. Aceh, as a special region, is endowed with broader authority through qanun and reusam to regulate governmental and societal matters. This study aims to examine the position of qanun and reusam within Indonesia's legal framework and their role in handling cases involving children in conflict with the law in Aceh. The research employs a normative juridical methodology with a descriptive-analytical approach, drawing on secondary data such as legislation, books, and publications related to qanun and reusam. The findings reveal that qanun and reusam play a significant role in addressing cases involving children in conflict with the law in Aceh. They emphasize the principles of diversion and restorative justice, focusing on resolving cases outside the formal judicial system and involving traditional, religious, and community leaders. Qanun and reusam support non-formal case resolution mechanisms rooted in local wisdom and values. Thus, qanun and reusam not only provide a framework for the region to exercise regional autonomy but also ensure the protection of children's rights in Aceh within the sphere of criminal law.